2020
DOI: 10.1097/sla.0000000000004558
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Hepatic and Regional Arterial Chemotherapy in Patients Who Underwent Curative Colorectal Cancer Resection

Abstract: Objective: To evaluate the effects of the addition of preoperative hepatic and regional arterial chemotherapy (PHRAC) on prognosis of stage II and III colorectal cancer (CRC) in a multicenter setting. Summary of Background Data: Our previous single-center pilot trial suggested that PHRAC in combination with surgical resection could reduce the occurrence of liver metastasis (LM) and improve survival in CRC patients. Methods: A prospective multi-center randomized controlled trial was conducted from December 2008… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 35 publications
(75 reference statements)
2
19
0
Order By: Relevance
“… 20 However, the efficacy of intraoperative or postoperative PVIC in preventing postoperative LM in patients with CRC is controversial; therefore, it is currently rarely performed. 11 The results of our meta‐analysis suggested that PVIC had no obvious advantages in preventing LM and failed to show satisfactory results in postoperative OS and DFS and even increased the risk of hepatic toxicity. However, PVIC improved the rates of patient mortality and CRC recurrence during the follow‐up period.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“… 20 However, the efficacy of intraoperative or postoperative PVIC in preventing postoperative LM in patients with CRC is controversial; therefore, it is currently rarely performed. 11 The results of our meta‐analysis suggested that PVIC had no obvious advantages in preventing LM and failed to show satisfactory results in postoperative OS and DFS and even increased the risk of hepatic toxicity. However, PVIC improved the rates of patient mortality and CRC recurrence during the follow‐up period.…”
Section: Discussionmentioning
confidence: 84%
“…Only 19 studies met the eligibility criteria and were included in the final analysis. 8 , 11 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 Gray literature was also searched; however, none met the inclusion criteria.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Metastatic Colorectal cancer (mCRC) is the third leading cause of cancer death globally, and the incidence of CRC, particularly mCRC, is increasing among younger people ( 2 , 3 ). Patients with localized CRC have a 5-year survival rate of 85% to 90%, while the mCRC patients were just about 12-14% ( 4 , 5 ). Finding reliable prognostic indicators to select high-DDRscore mCRC patients is critical for improving survival rates.…”
Section: Introductionmentioning
confidence: 99%